Effect of phosphodiesterase inhibitors in the bladder - Bilal Chughtai; Aizaz Ali; Claire Dunphy; Steven A. Kaplan (Asian Journal of Urology)
Many aging men will experience lower urinary tract symptoms (LUTS). Phosphodiesterase type 5 (PDE5) inhibitors have shown promise in treating LUTS in these patients. PDE5 inhibitors mediate their effects through several pathways including cAMP, NO/cGMP, K-channel modulated pathways, and the l-cysteine/H2S pathway. PDE5 inhibitors exert their effect in muscle cells, nerve fibers, and interstitial cells (ICs). The use of PDE5 inhibitors led to improvement in LUTS. This included urodynamic parameters. PDE5 inhibitors may play a significant role in LUTS due to their effect on the bladder rather than the prostate.